PEMBERIAN REMITAN OLEH MIGRAN UNTUK YADNYA DI DESA PAKRAMAN ASAL SUATU STUDI KASUS REMITAN MIGRAN DESA PAKRAMAN BERATAN DI DAERAH PROPINSI BALI - Kawi, Gde (PIRAMIDA, 2012)
This research, with the case study of the Bratan pakraman village migrants, aims at knowing and getting explanation about migrant?s condition as the remittance giver for yadnya, and the allocation of remittance for yadnya in the paktaman village of origin.Factors of the pakraman -village migrant significantly affect a) the gift of remittance for yadnya by migrant in the pakraman -village of origin, (b) the parhyangan usefulness, c) the pawongan usefulness, and (d).the palemahan usefulness. By migration, the condition of pakraman village migrant as a remittance giver for yadnya in the pakraman village of origin becomes better. The average of migrant?s monthly income in destination region is Rp 1,.291,950, the remittance allocation for parhyangan, pawongan, and palemahan consecutively are 2.170 %, 1.184 %, and 0.280 % of income Remittance that cannot be separated from migrant, doing yadnya in the pakraman village of origin is important for doing yadnya in the pakraman village of origin. This information is needed to be informed to the pakraman village society. It must be understood as a supporter for living in the trihitakarana environment system in the pakraman village of origin. Getting employment and income in the destination area is importance for Balinese Hindu in making material and spiritual well being
Keywords: remittance, yadnya and pakraman village